Actin filament turnover drives leading edge growth during myelin sheath formation in the central nervous system - Nawaz, Schanila (Dev Cell, 2015)
During central nervous system development, oligodendrocytes wrap their plasma membrane around axons to generate multi-lamellar myelin sheaths. To drive growth at the leading edge of myelin at the interface with the axon, mechanical forces are necessary, but the underlying mechanisms are not known. Using an interdisciplinary approach that combines morphological, genetic and biophysical analyses, we identified a key role for actin filament network turnover in myelin growth. At the onset of myelin biogenesis, F-actin is redistributed to the leading edge, where its polymerization-based forces push out non-adhesive and motile protrusions. F-actin disassembly converts protrusions into sheets by reducing surface tension and in turn inducing membrane spreading and adhesion. We identified the actin depolymerizing factor ADF/Cofilin1, which mediates high F-actin turnover rates, as essential factor in this process. We propose that F-actin turnover is the driving force in myelin wrapping by regulating repetitive cycles of leading edge protrusion and spreading.